Causes of Coronary Angioplasty Denial in Patients Diagnosed with Significant Coronary Artery Disease in East Afghanistan - Shams, Akmal; Ibrahimi, Ikramullah; Chardiwal, Humayoun (Journal of Cardiology and Cardiovascular Medicine, 2024)
Coronary Artery Disease (CAD) is a leading cause of mortality worldwide, with coronary angioplasty being a crucial intervention for patients with significant disease. This study aimed to identify and analyze the causes of coronary angioplasty denial in patients with significant coronary artery disease in Afghanistan, focusing on demographic, socioeconomic, and clinical factors. A case-control study was conducted with a sample size of 213 patients diagnosed with significant CAD at tertiary care center in Afghanistan. The case group consisted of 106 patients who were denied angioplasty, and the control group included 107 patients who underwent the procedure. Data were collected on demographic characteristics, comorbidities, education, residence, functional status, income, and the reasons for angioplasty denial. Descriptive statistics and comparative analyses were performed to assess the factors associated with denial. The primary reasons for angioplasty denial were financial constraints (45.3%, p < 0.001), limited hospital facilities (15.1%, p = 0.045), patient refusal (23.6%, p < 0.001), and physician preference for conservative management (12.3%, p = 0.091). Denial rates were higher among patients who were older, had multiple comorbidities, were from rural areas, and had lower education and income levels. Illiteracy and cultural beliefs contributed significantly to patient refusal, while inadequate healthcare infrastructure disproportionately affected rural populations. Financial and infrastructural barriers are the leading causes of coronary angioplasty denial in Afghanistan, exacerbating disparities in healthcare access, particularly among low-income and rural patients. Addressing these issues through policy reforms, improved healthcare infrastructure, and targeted public health education is essential to reducing CAD-related morbidity and mortality in the country.